Development of PowerPoint Learning Media Using 3D Animation Features for Science Subjects at MTs Negeri 1 Sidenreng Rappang - Andi Nafiisah Nabilah Said; Nurmayanti Nurmayanti; Madaling Madaling (Universitas Muhammadiyah Enrekang, 2024)
Animated 3-dimensional PowerPoint is teaching material that is packaged interactively to foster student motivation and learning motivation. The aim of this research is to determine the results of the development of 3-dimensional animated PowerPoint and the level of validity and practicality of 3-dimensional animated PowerPoint in class VIII B science studies at MTs Negeri 1 Sidenreng Rappang. The method applied is Research and Development (R&D) with the ADDIE research and development model, which consists of five stages: analysis, design, development, implementation and evaluation. Data analysis in this research is quantitative data analysis in the form of questionnaires for material and media validators, questionnaires for teacher and student responses. The research results show that the results of the development of 3-dimensional animated PowerPoint are classified as very valid for use with an overall percentage of 95.5% and the results in the practicality test show that 3-dimensional animated PowerPoint meets the very practical criteria with a percentage value of 98%. This means that the 3-dimensional animated PowerPoint developed is suitable for use in class VIII B science learning at Mts Negeri 1 Sidenreng Rappang.